miR-1908 Dysregulation in Human Cancers - Shen, Jinze; Wu, Yuchen; Ruan, Wenjing; Zhu, Feng; Duan, Shiwei (Frontiers in Oncology, 2022)
MiR-1908 is a miRNA located in the intron of the fatty acid desaturase 1 (FADS1) gene. The expression level of miR-1908 is abnormal in many diseases such as cancer. miR-1908 can inhibit the expression of at least 27 target genes by binding to the 3’ untranslated region (3’ UTR) of target genes. miR-1908 is involved in the biological processes of cell proliferation, cell differentiation, cell apoptosis, cancer cell invasion, and metastasis. The expression of miR-1908 is regulated by 11 factors, including lncRNA HOTTIP, adipokines (TNF-α, leptin, and resistin), NF-κB, free fatty acid (FFA), cholesterol, stearoyl-CoA desaturase (SCD1), immune-related transcription factors (STAT1, RB1, and IRF1). The expression of miR-1908 is also affected by the anticancer drug OSW-1, growth hormone (GH), and the anticonvulsant drug sodium valproate. In addition, the aberrant expression of miR-1908 is also related to the prognosis of a variety of cancers, including non-small cell lung cancer (NSCLC), ovarian cancer (OC), breast cancer, cervical cancer, glioma, high-grade serous ovarian carcinoma (HGSOC), osteosarcoma, etc. This article summarizes the abnormal expression pattern of miR-1908 in various diseases and its molecular regulation mechanisms. Our work will provide potential hints and direction for future miR-1908-related research.